(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The aim of this research is to remove the ambiguity and risks associated with the securitization process that investors face during trading in the credit market. By looking at the securitization aspects, the investor can understand the market of securitized goods and the investment decisions they need during investment operations (bonds). Investors are largely absent from most of the asset securitization and risk involved. Many studies which dealt with the concept of securitization have focused on the securitization of the mortgage only, without circumventing to the important aspects that the investors’ interest is focused on which are the bonds out of mortgage. Therefore, this research came to shed light on the concept of securitization and its role in the management of credit risk in banks and its positive repercussions and to identify the negative aspects for the carrier and investor through the conclusions and some recommendations are reached